Prospects of employing modern European cultivars of spring bread wheat in the breeding for powdery mildew resistance in the Northwestern region of Russia - T. V. Lebedeva; E. V. Zuev; A. N. Brykova (Труды по прикладной ботанике, генетике и селекции)
Background. Powdery mildew of bread wheat caused by the fungus Blumeria graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal is a widespread foliar disease of wheat in regions with cool and wet climate. It infects the foliage, stem and spike of the wheat host and causes yield reduction. Breeding for resistance is the economical way to control this disease. The object of this work was to analyze spring cultivars of wheat (Triticum aestivum L.) for powdery mildew resistance and some productivity indicators.Materials and methods. The study involved 150 European spring bread wheat cultivars whose resistance to the fungus was assessed at the seedling, heading and flowering phases of plant development. The population of the fungus manifested virulence to Pm1, Pm2, Pm3a-d, Pm4a-b, Pm5a, Pm6, Pm7, Pm8, Pm9, Pm16 and Pm19, and avirulence to Pm12. The damage to seedlings was evaluated using the scale from 0 (no damage) to 4 (abundant pustules). Resistance of the adult plants was analyzed according to the scale from 9 (no damage) to 1 (abundant pustules).Results and conclusions. Of the 150 cultivars, resistance at the seedling stage was shown by 12,7%, and at the adult stage by 20,1%. The cultivars ‘Dacke’, ‘SW Estrad’, ‘Sparrow’ and ‘Aranka’ were resistant in all phases of plant growth. ‘Naxos’ was characterized by a short period from seedlings to heading. The cultivars ‘Aranka’, ‘Zuzana’, ‘Septima’, ‘Tercia’ and ‘Sparrow’ had short stems, while ‘Torka’, ‘Sparrow’ and ‘Pasteur’ – large grains.